Enhanced Web Page Ranking Method Using Laplacian Centrality - Jaganathan, B; Desikan, Kalyani (International Journal of Engineering and Technology, 2018)
In today's era of computer technology where users want not only the most relevant data but they also want the data as quickly as possible. Hence, ranking web pages becomes a crucial task. The purpose of this research is to find a centrality measure that can be used in place of original page rank. In this article concept of Laplacian centrality measure for directed web graph has been introduced to identify the web page ranks. Comparison between the original page rank and Laplacian centrality based Page rank has been made. Kendall's Â correlation co-efficient has been used as a measure to find the correlation between the original page rank and Laplacian centrality measure based page rank.Â Â